Factors Associated with Handwashing Behaviors During the COVID-19 Pandemic: An Analysis of the Community Health Survey in Korea - Soojung Jo RN, PhD; Soo-Yeon Han RN, PhD; Nancy Howe MSc (SAGE Publishing, 2023)
Introduction Handwashing is the most effective preventive behavior for coronavirus disease-19 (COVID-19) infection. However, research has shown the lower handwashing behaviors among Korean adults. Objectives This study aims to analyze factors associated with handwashing as a preventive behavior for COVID-19 infection based on the health belief model (HBM) and the theory of planned behavior (TPB) behavioral theories. Methods This secondary data analysis utilized the Community Health Survey developed by Disease Control and Prevention Agency conducted in 2020. Sampling method was stratified and targeted 900 people living in the territory of each community public health center. In total, 228,344 cases were used in the analysis. Handwashing behavior, perceived susceptibility, perceived severity, subjective norm, and influenza vaccine uptake were used in the analysis. Regression analysis using weighing strategy by stratification and domain analysis was used. Results Less washing hand was associated with older age ( B  = 0.01, p  < .001), males ( B  = 0.42, p  < .001), not receiving an influenza vaccine ( B  = 0.09, p  < .001), perceived susceptibility ( B  = 0.12, p  < .001), subjective norm ( B  = 0.05, p  < .001), and perceived severity ( B  = −0.04, p  < .001). Conclusion While perceived susceptibility and social norm had positive association, perceived severity had a negative association with handwashing. Considering the Korean culture, creating a shared norm for frequent handwashing could be beneficial to promote handwashing rather than emphasizing the disease and its consequences.